Soil CO₂ Measurements and their Application in Karst Studies - Crann, David Lawrence (My University, 1982)
Soil CO₂ concentrations and soil temperature data were collected at the main field site, Rock Chapel Sanctuary, over a period of six months (July-December, 1981). Measurements were made under three vegetation types and at depths of 10, 25, and 50 cm beneath each vegetation type. Analysis of variance testing of the data set shows that at Rock Chapel soil temperature is not a significant source of variation in CO₂ concentrations. Furthermore depth beneath the soil, but not vegetation type, was found to be a significant source of variance in CO₂.
As a secondary part of the project the Dräger and vacutainer methods of soil air sampling were tested and compared. Both methods were found to be approximately equal in accuracy. The vacutainer method suffers from storage and internal pressure problems however it is a useful method when collecting large numbers of samples from permanent sites. The Dräger method is invaluable in remote locations and works best with small sample volumes.
The collection of soil CO₂ data should be done according to a well constructed sampling design otherwise much information regarding the effects of depth, vegetation type and other factors on CO₂ concentrations will be lost.
Keywords: geography; soil; CO₂, carbon dioxide; Karst studies; Rock Chapel Sanctuary